Effectiveness And Sustainability Of Baitul Mal Wat Tamwil Financing In The Development Of Micro-Enterprises In Central Java, Indonesia - Widiyanto, Widiyanto (2007)

(untitled)
The objective of this study is to examine the effectiveness and sustainability of BMT financing in developing micro-enterprises. Specifically, this study provides an evidence of technical efficiency of BMTs in Central Java and the effectiveness, impact and social benefits of BMT financing. Using non-parametric data envelopment analysis (CCR and BCC models), it is found that technical efficiency of BMTs for the period 2002-2005 is relatively low. The scale efficiency indicates that BMTs operate far below the optimal scale (i.e., 67.00 percent, 78.40 percent, 74.30 percent, and 80.9 percent in 2002, 2003, 2004, and 2005 respectively). The results also show that the gap in efficiency scores exist in both CCR and BCC models. It implies that BMTs use their inputs sub-optimally. Hence, under increasing return to scale, BMT can improve their performance by increasing their inputs; while under decreasing return to scale BMT can improve their performance by decreasing their inputs. The results suggest that BMT financing (Islamic financing) was effective in developing micro-enterprises. The results of paired sample t-test indicate that BMT financing was able to enhance business performance of micro-enterprises significantly by increasing business income, business profit, business asset and number of employees. In addition, the development of micro-enterprises also was able to reduce the rate of non-performing financing. The rate of non-performing financing is less than five percent. This indicates that micro-enterprises generally were able to develop their business so that they could repay the financing. The results suggest that selection process, business control, incentive system and good relationship construction (cooperation) constitute important factors in increasing the effectiveness of Islamic financing. Furthermore, the effectiveness of Islamic financing still can be improved by including non-performing financing control mechanism in the management system.